Rectal cancer treatment - Büchler, Markus W. (Recent results in cancer research, 2005)
Rectal cancer is one of the most prevalent cancers world-wide. It is also a paradigm for multimodal management, as the combination of surgery, chemotherapy and radiotherapy is often necessary to achieve the optimal outcome. Recently, international experts met in Heidelberg, Germany to discuss the latest developments in the management of rectal cancer, including the anatomic and pathologic basis, staging tools, surgical concepts including fast-track surgery and laparoscopic resection, functional outcome after surgery and the role of radio- and chemotherapy. This monograph summarizes this meeting and gives an extensive overview of the current concepts in management of rectal cancer. Postoperative pathophysiology and choice of incision -- Fast-track colonic surgery: status and perspectives -- Fast-track surgery: the heidelberg experience -- Rectal cancer: a compartmental disease. the mesorectum and mesorectal lymph nodes -- The pathological assessment of total mesorectal excision: what are the relevant resection margins? -- Is the lateral lymph node compartment relevant? -- Diagnostics of rectal cancer: endorectal ultrasound -- Preoperative staging of rectal cancer: the mercury research project -- Rectal cancer management: europe is ahead -- Teaching efforts to spread TME surgery in sweden -- Learning curve: the surgeon as a prognostic factor in colorectal cancer surgery -- Surgical results of total mesorectal excision for rectal cancer in a specialised colorectal unit -- Total mesorectal excision: the heidelberg results after TME -- Is local excision of T2/T3 rectal cancers adequate? -- Operative treatment of locally recurrent rectal cancer -- Laparoscopic TME: better vision, better results? -- Laparoscopic TME—the surgeon's or the patient's preference -- Laparoscopic total mesorectal excision—The turin experience -- Evacuation of neorectal reservoirs after TME -- Long-term functional results after straight or colonic j-pouch coloanal anastomosis -- Urinary and sexual function after total mesorectal excision -- Functional results of the colon j-pouch versus transverse coloplasty pouch in heidelberg -- Indications for neoadjuvant long-term radiotherapy -- Neoadjuvant radiotherapy and radiochemotherapy for rectal cancer -- Adjuvant radiochemotherapy for rectal cancer -- Intraoperative radiotherapy for rectal carcinoma -- Indications and effect on survival of standard chemotherapy in advanced colorectal cancer -- New chemotherapeutic strategies in colorectal cancer -- Active specific immunotherapy in colon cancer -- Radiofrequency ablation in metastatic disease.